2015
DOI: 10.1002/prp2.166
|View full text |Cite
|
Sign up to set email alerts
|

Maackiain is a novel antiallergic compound that suppresses transcriptional upregulation of the histamine H1 receptor and interleukin‐4 genes

Abstract: Kujin contains antiallergic compounds that inhibit upregulation of histamine H1 receptor (H1R) and interleukin (IL)-4 gene expression. However, the underlying mechanism remains unknown. We sought to identify a Kujin-derived antiallergic compound and investigate its mechanism of action. The H1R and IL-4 mRNA levels were determined by real-time quantitative RT-PCR. To investigate the effects of maackiain in vivo, toluene-2,4-diisocyanate (TDI)-sensitized rats were used as a nasal hypersensitivity animal model. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…We have demonstrated that PKCδ signaling is involved in PMAinduced upregulation of histamine H1 receptor (H1R) gene expression in HeLa cells and compounds, including quercetin and (-)-maackiain, suppressed H1R gene expression through the inhibition of PKCδ signaling (17)(18)(19). Thus, suppression of PKCδ signaling by these compounds could improve diabetic symptoms and help to further elucidate the mechanisms underlying these actions to better understand the role of PKCδ signaling in diabetes onset and progression.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that PKCδ signaling is involved in PMAinduced upregulation of histamine H1 receptor (H1R) gene expression in HeLa cells and compounds, including quercetin and (-)-maackiain, suppressed H1R gene expression through the inhibition of PKCδ signaling (17)(18)(19). Thus, suppression of PKCδ signaling by these compounds could improve diabetic symptoms and help to further elucidate the mechanisms underlying these actions to better understand the role of PKCδ signaling in diabetes onset and progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, anti-allergic activity of (Ϫ)-maackiain had not yet been reported. We have shown that (Ϫ)-maackiain is the prominent component responsible for the anti-allergic activity of Kujin (14). Because (Ϫ)-maackiain did not show any antioxidant activity or inhibit PKC␦ enzymatic activity, it is likely that its anti-allergic activity proceeded through an unknown mechanism.…”
Section: Discussionmentioning
confidence: 91%
“…Rats-Previously, we have demonstrated that pretreatment with racemic maackiain and quercetin suppresses TDI-induced nasal symptoms and up-regulation of H1R and IL-4 gene expression in TDI-sensitized rats (8,14). In the present study, we investigated the effect of an additional Hsp90 inhibitor, celastrol, on TDI-induced nasal symptoms and up-regulation of H1R and IL-4 gene expression in the nasal mucosa of TDIsensitized rats.…”
Section: Effect Of Celastrol On Tdi-induced Nasal Symptoms and Upregumentioning
confidence: 89%
See 1 more Smart Citation
“…304 kDa이다. Chiisanoside은 소장(small intestine)에서 지방 흡수를 방해하는 생물학적 기능이 있다 [13]. Corynoline의 알 려진 생물학적 기능은 세포간 결합을 방해하는 것이다 [7].…”
unclassified